Analysis of Service Quality of Indonesian Workers Placement and Protection Service Center Semarang in Placement of Indonesian Migrant Workers - Tissa Silvia; Budi Puspo Priyadi; Ida Hayu Dwimawanti (Jurnal Administrasi Publik (Public Administration Journal), 2020)
The Indonesian Workers Placement and Protection Service Center Semarang is the Indonesian Workers Placement and Protection Service Center which houses Indonesian labor services in the Central Java Province. The problem of the rise of illegal migrant workers, the processing of documents which still requires a long time, the high placement of Indonesian workers in the informal sector and the still high complaints of Indonesian workers in the Semarang Indonesian Placement and Protection Workforce Service Center show that there are still many problems with migrant workers. This study aims to identify the service quality of the Semarang Indonesian Workers Placement and Protection Service Center provided to Indonesian workers. This type of research is qualitative research. Data collection techniques used through interviews, observation and documentation. Sources of data used through primary and secondary data. The results of this study are the responsiveness dimension of the Indonesian Workers Placement and Protection Service Center can realize the pre-departure process in an average of one month, the insurance dimension is still a problem related to service convenience, tangibles dimension has been effectively seen from the competency test facilities and the final debriefing, the empathy dimension needs a little improvement on the acceptance of service input, the reability dimension is quite good with the certainty of costs but an evaluation of HR related needs.